A Case Report of Hydrocephalus in a US Military Recruit. Issue 9 (10th July 2020) - Clerc, Jacqueline; Harp, Garrett M; Cathey, Michael; Bauer, Matthew
ABSTRACT: We present a case of chronic non-communicating hydrocephalus (NCH) in a US military recruit. Non-communicating hydrocephalus is a pathologic obstruction of cerebrospinal fluid (CSF) resulting in enlargement of the ventricles and elevated intracranial pressure. The patient is an 18-year-old male recruit who was evaluated in the Naval Medical Center emergency room for left hip pain and incidentally was found to have profound ventriculomegaly on head imaging. The diagnosis and evaluation of hydrocephalus is greatly dependent on clinical history and supported by radiographic imaging. Based on these factors, one can determine if the hydrocephalus is either acute or chronic and communicating or non-communicating.